Multi-Institutional Arrangements in Health Care: Review, Analysis, and a Proposal for Future Research - Fottler, Myron D.; Schermerhorn, John R.; Wong, John; Money, William H. (Academy of Management Review, 1982)
Multi-institutional arrangements in the health care industry have grown rapidly over the past 10 years. This paper provides a literature review and a research proposal concerning the managerial aspects of this phenomenon.